Pemerintah Daerah Provinsi Riau dan Hukum Adat Melayu Riau Menurut Teori Eksistensi Karl Jaspes - Hengki Firmanda; Juhansar Andi Latief (Al-Ulum, 2018)
This study aims at analyzing the relationship between Riau provincial governments and Riau Malay Customary Law (LAM Riau) using Jaspers’ theory of existence. The data of this study are qualitative ones using the sociological law as the approach. Riau Malay customary law is the norm regulates the manner of behavior of the Malay people. Riau Malay customary law is a law-based-community. It means, the law is conserved and raised its existence jointly. The local governments have a very important role in maintaining its existence. Local governments (executive and legislative) and customary institution are defined as state organizers.